Perbandingan Pengaruh Working Capital to Total Assets (WCTA), Operating Income to Total Liabilities (OITL), dan Return on Equity (ROE) Terhadap Pertumbuhan Laba Pada Perusahaan Jasa Sub Sektor Transportasi dan Sub Sektor Konstruksi dan Bangunan Yang Terda - Gantino, Rilla; Dewi, Melinda Kusuma (Jurnal Riset Akuntansi, 2019)
Abstract. This study aimed to analyze the effect of working capital to total assets (WCTA), operating income to total liabilities (OITL), and return on equity (ROE) on profit growth in transportation companies and construction and building companies listed on the Stock Exchange for the 2013-2017 period. The method used is purposive and cluster sampling. This study used is secondary data from the financial statements. Data analysis method used is multiple linear regression analysis. The results show for transportation companies, working capital to total assets (WCTA) and operating income to total liabilities (OITL) have no significant effect on profit growth and return on equity (ROE) have significant positive effect on profit growth. On construction and building companies, working capital to total assets (WCTA) have significant negative effect on profit growth. Operating income to total liabilities (OITL) and return on equity (ROE) have no significant effect on profit growth. Simultaneously both show the same results, the independent variable (WCTA, OITL, and ROE) have a significant effect on the dependent variable (profit growth). Keywords: : working capital to total assets (WCTA), operating income to total liabilities (OITL), return on equity (ROE), profit growth